ChemInform Abstract: An Odorless Thia‐Michael Addition Using Bunte Salts as Thiol Surrogates. Issue 32 (August 2015) - Lin, Ya‐mei; Lu, Guo‐ping; Cai, Chun; Yi, Wen‐bin
Abstract The synthesis of various β‐sulfido carbonyl compounds via hydrolysis of Bunte salts is described.